2021
DOI: 10.1016/j.redox.2020.101815
|View full text |Cite
|
Sign up to set email alerts
|

Altered glucose metabolism and cell function in keloid fibroblasts under hypoxia

Abstract: Keloids exhibit metabolic reprogramming including enhanced glycolysis and attenuated oxidative phosphorylation. Hypoxia induces a series of protective responses in mammalian cells. However, the metabolic phenotype of keloid fibroblasts under hypoxic conditions remains to be elucidated. The present study aimed to investigate glycolytic activity, mitochondrial function and morphology, and the HIF1α and PI3K/AKT signaling pathways in keloid fibroblasts (KFB) under hypoxic conditions. Our results showed that hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 48 publications
(43 reference statements)
3
63
0
Order By: Relevance
“… 46 , 47 This is because hypoxia can significantly affect mitochondrial activity, impairing muscle energy generation through oxidative phosphorylation, where oxygen is required as an electron‐terminal receptor, resulting in a decrease in adenosine triphosphate (ATP), which is required for protein synthesis and muscle contraction. 48 , 49 , 50 …”
Section: Pathophysiology Of Muscle Damagementioning
confidence: 99%
“… 46 , 47 This is because hypoxia can significantly affect mitochondrial activity, impairing muscle energy generation through oxidative phosphorylation, where oxygen is required as an electron‐terminal receptor, resulting in a decrease in adenosine triphosphate (ATP), which is required for protein synthesis and muscle contraction. 48 , 49 , 50 …”
Section: Pathophysiology Of Muscle Damagementioning
confidence: 99%
“…For glycolysis in keloids, Wang et al showed that in hypoxia-promoted proliferation, GLUT-1 expression was enhanced, as well as migration and collagen synthesis, and autophagy in KF [66]. However, in that study, no blocking measures for GLUT-1 or other glycolytic enzymes were performed.…”
Section: Discussionmentioning
confidence: 94%
“…ROS is associated with increased expression of the GLUT1 glucose transporter in the skin of patients affected by diabetes [ 26 ], psoriasis [ 27 ], and keloids [ 16 ], thereby providing a biochemical marker for oxidative stress and the potential for developing fibroproliferative lesions. Increased ROS in fibroblasts from keloid scar tissue exposed to hypoxia [ 28 ] also suggests that oxidative stress likely plays an important role in the development and maintenance of keloids. Figure 3 demonstrates the connection between ROS and alterations in DNA and fibroblasts for hypertrophic-keloid scarring and carcinogenesis.…”
Section: Reviewmentioning
confidence: 99%